Weather conditions during Athens Olympic rowing and flatwater canoe-kayak regatta at the Olympic rowing center in Schinias - Diafas, V.; Kaloupsis, S.; Bachev, V.; Dimakopoulou, E.; Diamanti, V. (Kinesiology, 2006)
In water sports like rowing and canoe-kayak weather conditions are important factors to the competition and can probably reduce the performance of athletes. Thus, the aim of this study was to analyze the weather conditions during August and September in the past 10-13 years in the Schinias area where the Olympic Rowing and Canoe-Kayak Regattas were held. A secondary aim was to relate the data with the environmental conditions from previous Olympic Games. Wind speed (m/s), relative humidity (%) and temperature (oC) daily from 800 to 2100 were recorded and collected from the National Meteorological Bureau. The results revealed that the wind speed was under 5m/s during races and training hours, temperature and humidity were 29oC and under 60%, respectively. However, there were some exceptions in the weather but during the Olympic Games 2004, the weather conditions were normal and the athletes participated in the competition without problems.